Condylar growth and mandibular positioning with stepwise vs maximum advancement - Hagg, U.; Rabie, A.B.M.; Bendeus, M.; Wong, R.W.K.; Wey, M.C.; Du, X.; Peng, J. (Elsevier, 2008)
Introduction: The aim of this study was to compare the effects of several Class II malocclusion treatments on condylar growth and positioning of the mandible. Methods: The material comprised series of lateral cephalograms obtained at the start, after about 6 months, and after about 12 months of treatment from 3 groups of consecutively treated patients who used a headgear-activator with stepwise mandibular advancement (HGA-S), a headgear-activator with maximum jumping of the mandible (HGA-M), and a headgear-Herbst appliance with stepwise advancement (HGH-S), respectively. Six-month growth data from matched controls were used to calculate the net treatment effects. Results: Mandibular prognathism was enhanced after stepwise advancement but not after maximum jumping, and only during the initial phase of therapy; the effect was significantly greater for the fixed functional appliance than for the removable functional appliance. Lower-facial height was increased by the HGA-S, unchanged by the HGA-M, and restrained by the HGH-S. The low construction bite of the HGH-S meant that the extent of bone apposition on the posterior and superior parts of the condyle was similar, whereas the high construction bite of the HGA-S and the HGA-M meant that the effect on the superior part was greater, but only significantly so after stepwise advancement. Conclusions: The mode of jumping, the vertical opening, and whether the functional appliance is fixed or removable affect the amount and pattern of condylar growth, and the position of the mandible. (Am J Orthod Dentofacial Orthop 2008;134:525-36)